The Influence Of Environmental, Social And Governance (ESG) Performance On The Severity Of Losses And The Recovery Time Of Stock During The Crisis Of The Covid-19 Pandemic In Southeast Asia - Khalilul Rahman; Asniati Bahari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to examine the effect of environmental, social and governance (ESG) performance on loss severity and recovery time of non-financial companies in Southeast Asia during the Covid-19 pandemic crisis in 2020-2021. The number of observations in this study is 1010, with 662 companies in 2021 and 348 companies in 2020. This study uses a quantitative method with secondary data obtained from Refinitiv Eikon Thomson Reuters. Unbalanced panel data regression analysis was performed using STATA version 17. The results showed that ESG performance and environmental performance had a positive and significant effect on the severity of losses and stock recovery during the crisis. Social performance has no effect on the severity of losses and recovery time during a crisis. Governance performance has no effect on the severity of losses, but has a positive and significant effect on the stock recovery time during a crisis. These findings indicate that investors in Southeast Asia have not prioritized the ESG aspect in their investment decisions, and even consider it as a burden or short-sighted investors. This research recommends to investors to develop investment strategies based on socially responsible investment and to regulators to develop a better and more detailed framework related to assessing ESG performance.